Health Education with Videos on Drug Adherence in the Elderly with Hypertension - Achjar, Komang Ayu Henny; Putu Ayu Erika Prameswari; Agus Sri Lestari; Nyoman Ribek; Ketut Gama; I G. K. Gede Ngurah; Ni Ketut Nuratni (Journal of Education Reseach and Evaluation, 2024)
Adherence to medication in the elderly with hypertension is often a challenge, which can increase the risk of complications. The purpose of this study is to evaluate the effect of health education through video on medication adherence in the elderly at Puskesmas I East Denpasar. This study uses a quantitative research design with a pre-experimental approach. The subjects of the study were 53 elderly people with hypertension. Data collection was carried out before and after the intervention using educational videos, with instruments in the form of medication compliance questionnaires. Data analysis was carried out using the Wilcoxon statistical test. Before the education, the majority of respondents showed low compliance (52.8%). After the intervention, the high compliance rate increased significantly to 67.9%, while the low compliance decreased to 13.2%. The results of the Wilcoxon test showed a p-value = 0.000, indicating a significant influence of video education on medication adherence. Health education through videos is effective in increasing medication adherence in the elderly with hypertension. The implications of this study encourage the application of similar educational methods to improve therapy adherence in various health settings.